Building a Healthy Generation by Making Mackerel Fish Nuggets and Anti-Stunting Mading - Anshari, Muhammad; Ardli, Ahmad Qolbi; Laisa, Alya; Mubarak, Muhammad Rusydi; Khairunnisa, Najla; Azizah, Nor; Putri, Novita Rahmadani (UrbanGreen Central Media, 2024)
The problem of stunting is still a big challenge in efforts to improve children's health in Indonesia, especially in rural areas. This program aims to increase awareness of the people of Sigam Village, Kotabaru Regency, regarding the importance of balanced nutrition to prevent stunting in toddlers and support the health of pregnant women. Two main approaches are carried out in this program: (1) making educational magazines displaying information about healthy eating patterns and the impact of stunting, and (2) making and distributing mackerel fish nuggets as a nutritious food alternative for toddlers and pregnant women. Antistunting posters were installed at the Sigam Village Kindergarten so that they can be easily accessed by parents and caregivers, with the hope of increasing their understanding of nutrition and examples of balanced menus that can be applied in everyday life. The mackerel fish nuggets distributed are made from local ingredients with high protein and omega-3 content which are useful for supporting children's growth and the health of pregnant women. Program evaluation shows a positive response from the community, who feel helped in understanding the importance of nutritional intake and choosing affordable nutritious food. This program has succeeded in increasing public awareness and understanding of the importance of nutrition to prevent stunting, as well as providing practical nutritious food solutions that children like. It is hoped that this activity can continue to be implemented and involve more parties to create a generation that is healthy and free from the risk of stunting.